TINGKAT PENGETAHUAN IBU NIFAS TENTANG METODE AMENORE LAKTASI (MAL) DI KLINIK BERSALIN AISYAH MEDAN TAHUN 2016 - Rhina Chairani Lubis (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Effectiveness of Lactation Amenorrhea Method (MAL) 89% for exclusively breastfeeding mothers. In Indonesia the achievement of MAL is still low as measured by the achievement level of exclusive Asi which is still low. The study was conducted at the Aisyah Maternity Clinic which aims to determine the level of knowledge of postpartum mothers about the lactation Amenorrhea Method (MAL). Research is descriptive using a questionnaire. The population was all postpartum mothers visiting the Aisyah Maternity Clinic as many as 30 people. Sampling is done by accidental sampling. Data analysis was carried out descriptively.The results showed that the majority of mothers' knowledge was enough, namely 18 respondents (60%), the majority of the age of 20-35 years (87%), the majority of high school/vocational education 16 respondents (53%), multipara majority majority 22 respondents (73%), source of information for the majority of health workers 21 respondents (70%). Based on the above research, it can be concluded that the level of knowledge of postpartum mothers about the lactation Amenorrhea Method (MAL) in the Aisyah Maternity Clinic is sufficiently knowledgeable. It is recommended to postpartum mothers so that they can add insight into the Lactation Amenorrhea Method (MAL)